Financial Health Check-up of Pokhara Royal Co-operative Society Limited in the Framework of PEARLS - Baral, Keshar J. (Journal of Nepalese Business Studies, 2007)
Using the data set disclosed in annual reports and extracted from the ledger of Pokhara Royal Cooperative Society Limited (PRCSL), this paper examines the financial health of PRCSL in the framework of PEARLS. The health check up conducted on the basis of publicly available financial data concludes that PRCSL has not earned enough to pay up the return on member share capital and build up the institutional capital as the second line of defense for saving deposits of member-clients. In addition, the perusal of indicators of different components of PEARLS indicates that the financial health of PRCSL is not so sound. Journal of Nepalese Business Studies 2006/III/1 pp. 45-69